1983
DOI: 10.1177/070674378302800507
|View full text |Cite
|
Sign up to set email alerts
|

Two Year Follow-Up Study of an Outreach Program in Geriatric Psychiatry*

Abstract: In Canada and the U.S. the percentage of elderly people is increasing and more funds are being spent on institutional programs. Yet many are not so impaired that they cannot be looked after by relatives. A number of community outreach programs are available. From an inpatient psychogeriatric unit in Hamilton Provincial Hospital an outreach program is described. A follow-up study was done during a 2 year period by contacting the referral sources. The 24% who had been admitted were compared with the 75.9% who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Next were patients with major depression, with a mean change of 1 .O. However, this change was the only one that was not statistically significant, a finding which concurs with that of Houston (1983), who found that patients with affective disorders were relatively resistant to community treatment. Alternatively, since depression in the elderly is often slower to respond to treatment than depression in younger people, our three-month assessment may have been too early to identify late responders.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Next were patients with major depression, with a mean change of 1 .O. However, this change was the only one that was not statistically significant, a finding which concurs with that of Houston (1983), who found that patients with affective disorders were relatively resistant to community treatment. Alternatively, since depression in the elderly is often slower to respond to treatment than depression in younger people, our three-month assessment may have been too early to identify late responders.…”
Section: Discussionsupporting
confidence: 75%
“…The results of other studies are more encouraging (Houston, 1983;Levy, 1985;Moreno and Wile, 1989; Wasylenki e t al., 1984). There is a consensus that comprehensive community care of psychogeriatric patients minimizes unnecessary admission to hospital, and that high levels of satisfaction with such services are reported by carers.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…A non-randomized retrospective Canadian study compared the 2-year outcome of patients treated by a psychogeriatric outreach service with those admitted to a psychogeriatric unit. Older people with affective disorders managed in the community had a poorer outcome than the hospitalized group, although there was less institutionalization of the community cases (Houston, 1983). These findings should be interpreted with great caution because of the study's methodological shortcomings.…”
Section: The Decision To Admit: Hospital-or Community-based Treatment?mentioning
confidence: 78%